Increasing Red Brick Production in The Home Red Brick Industry in Dengkol Village, Singosari District, Malang Regency - Alamsyah, Alik Ansyori; Darmawan, Azhar Adi (OMNICODE Journal (Omnicompetence Community Developement Journal), 2025)
Dengkol Village, Singosari District, Malang Regency has more than four home industries/brick industry centers. The business that started in 2005 started from the hereditary business of Mr. Subadi, which was finally managed together with the family with the aim of providing a forum and activities for the youth of Karang Taruna Village in Dengkol Village, Singosari District, Malang Regency to boost the village economy. Problems that are still encountered in the home industry of bricks in Dengkol Village, Singosari District, Malang Regency, include; product quality that is still inconsistent in every production process, uncertain selection of material quality, no good management and marketing (sales are still passive) and very limited product variations. The solution to the problems in this home industry is to provide re-mentoring to home industry workers about the correct procedure for making bricks according to SNI 15-2094-2000, provide guidance on proper management, production financing circulation flow until it is known when this home industry experiences Break Event Point and experiences constant business profits. In this activity, the results that have been obtained are the increasing quality and quantity of brick making managed by families and youth of the Dengkol Village Youth Organization, Singosari District, Malang Regency.